Juvenile Justice Reform and the Principle of Best Interests of the Child: A Global Legal Perspective - Mujiono, Mujiono; Marliyati, Marliyati; Santosa, Tomi Apra; Dewi, Mira Nila Kusuma; Ghoni, Abdul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The reform of juvenile justice systems has become a central concern in global legal discourse, particularly in aligning legal practices with the universally recognized principle of the best interests of the child. This study provides a comparative legal analysis of juvenile justice reforms across various jurisdictions, evaluating the extent to which domestic legal frameworks integrate and operationalize this principle in both legislation and judicial practice. Utilizing a normative-qualitative approach, the research examines international legal instruments—such as the United Nations Convention on the Rights of the Child (CRC)—and their influence on national juvenile justice policies in both developed and developing countries. The findings reveal significant disparities in implementation, with some systems emphasizing rehabilitation and diversion, while others retain punitive models that compromise children's rights. The study concludes that effective juvenile justice reform requires not only legal alignment with international standards but also the establishment of child-sensitive institutions, specialized training for legal professionals, and a holistic approach that considers the child’s social context. This research underscores the imperative of embedding the best interests of the child as a guiding norm in both procedural and substantive aspects of juvenile justice worldwide.